Force level of small diameter nickel-titanium orthodontic wires ligated with different methods - Rodrigo Hitoshi Higa; José Fernando Castanha Henriques; Guilherme Janson; Murilo Matias; Karina Maria Salvatore de Freitas; Fernanda Pinelli Henriques; Manoela Fávaro Francisconi (SpringerOpen, 2017)
Abstract Background The aim of this study was to compare the deflection force in conventional and thermally activated nickel-titanium (NiTi) wires in passive (Damon Q) and active (Bioquick) self-ligating brackets (SLB) and in conventional brackets (CB) tied by two different methods: elastomeric ligature (EL) and metal ligature (ML). Methods Two wire diameters (0.014 and 0.016 in.) and 10 specimens per group were used. The specimens were assembled in a clinical simulation device and tested in an Instron Universal Testing Machine, with a load cell of 10 N. For the testing procedures, the acrylic block representative of the right maxillary central incisor was palatally moved, with readings of the force at 0.5, 1, 2, and 3 mm, at a constant speed of 2 mm/min and temperature of 36.5 °C. Results The conventional NiTi released higher forces than the thermally activated NiTi archwires in large deflections. In general, the SLB showed lower forces, while the ML had higher forces, with both showing a similar force release behavior, constantly decreasing as the deflection decreased. The EL showed an irregular behavior. The active SLB showed smaller forces than passive, in large deflections. Conclusions The SLB and the ML exhibit standard force patterns during unloading, while the elastomeric ligatures exhibit a randomly distributed force release behavior.